Financial Feasibility and Sensitivity Analysis of Organic Rice Farming Based on the System of Rice Intensification (SRI) in Kolaka Regency Southeast Sulawesi, Indonesia - Samsul Alam Fyka; Britney Cristi (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
This study evaluates the financial feasibility and sensitivity of organic rice farming under the System of Rice Intensification (SRI) in Kolaka Regency, Southeast Sulawesi. Although previous studies have documented the economic performance of organic and SRI-based rice systems, integrated evidence combining profitability, break-even thresholds, and sensitivity analyses within specific agroecological contexts, particularly in eastern Indonesia, remains limited. This study addresses this gap by providing a context-sensitive financial assessment that emphasizes both efficiency and economic resilience. Farm-level cost income analysis, the Revenue Cost (R/C) ratio, the Break-Even Point (BEP), the Return on Investment (ROI), and sensitivity analysis were applied. The results show that the total production costs of IDR9.681.021 per hectare generated revenues of IDR38.214.300 per hectare, yielding a net income of IDR28.533.279 per hectare. The R/C ratio of 2.94 and ROI of 294.73% indicate strong financial performance; however, these values should be interpreted cautiously as location-specific outcomes rather than generalized benchmarks. BEP analysis reveals that actual production and market prices substantially exceed break-even levels, providing a considerable safety margin. Sensitivity analysis demonstrates that the farming system remains financially viable under moderate shocks, including price declines or cost increases of up to 20%. This study contributes by highlighting SRI-based organic rice farming as a mechanism for enhancing farm-level economic resilience through cost efficiency. Nevertheless, the single-location case study design limits broader generalization, suggesting the need for multi-region and longitudinal analyses in future research.